MUC1-C INTEGRATES PD-L1 INDUCTION WITH REPRESSION OF IMMUNE EFFECTORS IN NON-SMALL CELL LUNG CANCER - Bouillez, Audrey (Oncogene, 2017)
Immunotherapeutic approaches, particularly PD-1/PD-L1 blockade, have improved the treatment of non-small cell lung cancer (NSCLC), supporting the premise that evasion of immune destruction is of importance for NSCLC progression. However, the signals responsible for upregulation of PD-L1 in NSCLC cells and whether they are integrated with the regulation of other immune-related genes are not known. Mucin 1 (MUC1) is aberrantly overexpressed in NSCLC, activates the NF-κB p65→ZEB1 pathway and confers a poor prognosis. The present studies demonstrate that MUC1-C activates PD-L1 expression in NSCLC cells. We show that MUC1-C increases NF-κB p65 occupancy on the CD274/PD-L1 promoter and thereby drives CD274 transcription. Moreover, we demonstrate that MUC1-C-induced activation of NF-κB→ZEB1 signaling represses the TLR9, IFNG, MCP-1 and GM-CSF genes, and that this signature is associated with decreases in overall survival. In concert with these results, targeting MUC1-C in NSCLC tumors suppresses PD-L1 and induces these effectors of innate and adaptive immunity. These findings support a previously unrecognized central role for MUC1-C in integrating PD-L1 activation with suppression of immune effectors and poor clinical outcome.